Prevalence of thunderclap headache in patients with ruptured intracranial aneurysms: series of 60 cases - Esmanhotto, Bruno Bertoli (2019)
Thunderclap headache (TCH) is a head pain that begins suddenly and is severe at onset. TCH might be the first sign of subarachnoid hemorrhage. This study was conducted to evaluate the presence of thunderclap headache (TCH) in patients with ruptured intracranial aneurysm (RIA) and endovascular treatment (EVT). We evaluated the pattern of headache in 60 patients who suffered a RIA and EVT at time of admission and prospectively evaluated the characteristics of previous headache within one year before the rupture. Thirty-one patients (51,7 %) had TCH related to the rupture. Aneurysm size does not affect the occurrence of thunderclap headache (p=0,08). The vascular aneurysm territory is not related to presence of TCH (p=0,527). The prevalence of TCH in this cohort was similar to previous studies. All patients with acute thunderclap headache should be evaluated for subarachnoid hemorrhage.